2004
DOI: 10.1002/app.20621
|View full text |Cite
|
Sign up to set email alerts
|

Physical, mechanical, and thermal properties of PVC/PMMA blends in relation to their morphologies

Abstract: Abstract:The effect of blending poly (methyl methacrylate) (PMMA) in various proportions with suitably stabilized and plasticized poly (vinyl chloride) (PVC) was studied with reference to their physical, mechanical, and thermal properties. The resulting morphologies of the various blends were also studied to find a suitable explanation of these properties. The physical and mechanical properties of such polyblends revealed a substantial increase in toughness accompanied with unusual increase in modulus and ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 15 publications
1
37
0
1
Order By: Relevance
“…Figure 5 exhibits the shore D hardness of rigid and plasticized PVC/PMMA blends. It can be seen that the shore D hardness is influenced by the rigidity of PMMA; it increases almost linearly and progressively with increasing the amount of PMMA [17] . However the presence of the plasticizer decreases it strongly because of the flexibility of the polymeric chains.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…Figure 5 exhibits the shore D hardness of rigid and plasticized PVC/PMMA blends. It can be seen that the shore D hardness is influenced by the rigidity of PMMA; it increases almost linearly and progressively with increasing the amount of PMMA [17] . However the presence of the plasticizer decreases it strongly because of the flexibility of the polymeric chains.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…Paul and Barlow4 have suggested that the α hydrogen of PVC can interact with the ester carboxylate group (H bond acceptor of the acrylic polymer) to form hydrogen bond and is also a key factor in achieving miscibility 5. Also, there is a probability of interaction between the CCl dipole of PVC and the α hydrogen of the acrylate ester 6. These two phenomena can account for increased strength of the IPNs and thus interpenetrating networks of PVC and PBA can be expected to display improved tensile as well as toughness behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This is a consequence of a radical mechanism involving the formation of chlorine radical species that fail to form HCl as it interacts with the PMMA. Secondly, even if HCl is produced, again the interaction with PMMA generates anhydrides and metal chlorides that participate in the mechanism of neutralization . The second degradation stage, due to the scission of the polyenes resulting from the first degradation step, starts near to the random degradation of PMMA .…”
Section: Resultsmentioning
confidence: 99%